Communication Services for a Distributed Hospital Information System - Graeber, S. (Methods of Information in Medicine, 1996)
Planning principles and development are described of a communication server which controls and performs all information exchange between distributed and heterogeneous applications in a hospital information system. The analysis is based on business process modeling. At present, the core of the server uses a commercial product (Cloverleaf). This allows to connect both old systems with no or few interface features and new systems with modern interface facilities (such as HL7). Prerequisites, functions, and configuration of the server software are described in detail. Experiences, advantages, and disadvantages are discussed.
Keywords: Hospital Information System; Hospital Communication System; Communication Server; Business Process Modeling; Client-Server Architecture; HL7